The use of evaluation in an iterative process to support planning: the case of the New Skills Fund - Buscemi, Virgilio; Catapano, Francesca; Paris, Paola; Parisi, Alessandra Luisa; Quatrini, Dario; Teselli, Anna (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
The evaluation of the NOP SPAO 2014-2020, particularly the one on the interventions funded by the FNC, seems to suggest that program evaluation is more useful for decision-makers when integrated into an ongoing process. This paper aims to present the case and examine whether the enhanced effectiveness of public action can be attributed to the effective use of evaluation findings, which are based on a forward-looking approach that highlights success factors and governance ‘malfunctions’.